Complications of peritonsillar abscess - Tejs Ehlers Klug; Thomas Greve; Malene Hentze (BMC, 2020)
Abstract Background The vast majority of patients with peritonsillar abscess (PTA) recover uneventfully on abscess drainage and antibiotic therapy. However, occasionally patient´s condition deteriorates as the infection spread in the upper airway mucosa, through cervical tissues, or hematogenously. The bacterial etiology of PTA is unclarified and the preferred antimicrobial regimen remains controversial. The current narrative review was carried out with an aim to (1) describe the spectrum of complications previously recognized in patients with peritonsillar abscess (PTA), (2) describe the bacterial findings in PTA-associated complications, and (3) describe the time relation between PTA and complications. Methods Systematic searches in the Medline and EMBASE databases were conducted and data on cases with PTA and one or more complications were elicited. Results Seventeen different complications of PTA were reported. The most frequently described complications were descending mediastinitis (n = 113), para- and retropharyngeal abscess (n = 96), necrotizing fasciitis (n = 38), and Lemierre´s syndrome (n = 35). Males constituted 70% of cases and 49% of patients were > 40 years of age. The overall mortality rate was 10%. The most prevalent bacteria were viridans group streptococci (n = 41, 25%), beta-hemolytic streptococci (n = 32, 20%), F. necrophorum (n = 21, 13%), S. aureus (n = 18, 11%), Prevotella species (n = 17, 10%), and Bacteroides species (n = 14, 9%). Simultaneous diagnosis of PTA and complication was more common (59%) than development of complication after PTA treatment (36%) or recognition of complication prior to PTA (6%). Conclusion Clinicians involved in the management of PTA patients should be aware of the wide range of complications, which may arise in association with PTA development. Especially males and patients  > 40 years of age seem to be at an increased risk of complicated disease. In addition to Group A streptococci and F. necrophorum, the current findings suggest that viridans group streptococci, S. aureus, Prevotella, and Bacteroides may also play occasional roles in the development of PTA as well as spread of infection. Complications occasionally develop in PTA patients, who are treated with antibiotics and surgical drainage.